FEN ÖĞRETİM PROGRAMLARINDA ÇEVRE EĞİTİMİ: TÜRKİYE, KANADA, AMERİKA ÖRNEĞİ. - ERTEN, Sinan; KÖSEOĞLU, Pelin; GÖK, Bilge (Mehmet Akif Ersoy University Journal of Education Faculty)
The aim of this research is to reveal the similar and different aspects of environmental education attainments at the 5th, 6th, 7th and 8th grades in the science teaching program of Turkey (2018), Canada (2007) and the United States of America (2011). The holistic multiple case design was used in the research and the data were obtained through document analysis. Content analysis was used while analyzing the data. First of all, each of the science teaching program was examined in depth and the achievements related to environmental education were determined. The determined achievements were classified according to their grade levels, and their similarities and differences were determined and analyzed in depth. In the results of the research, it has been seen that Canada has an important and sufficient program for raising environmentally conscious individuals, while Nebraska does not have an adequate program. The Turkish Science Teaching Program was not evaluated as adequate as the Canadian Science Teaching Program. Suggestions have been made to further develop the 2018 Turkish Science Teaching Program in terms of environmental education.